AMPK/SIRT1 Pathway is Involved in Arctigenin-Mediated Protective Effects Against Myocardial Ischemia-Reperfusion Injury - Liu, Cheng-Yin; Zhou, Yi; Chen, Tao; Lei, Jing-Chao; Jiang, Xue-Jun (Frontiers in Pharmacology, 2021)
Arctigenin, one of the active ingredients extracted from Great Burdock (Arctium lappa) Achene, has been found to relieve myocardial infarction injury. However, the specific mechanism of Arctigenin against myocardial infarction remains largely unknown. Here, both acute myocardial ischemia-reperfusion injury (AMI/R) rat model and oxygen glucose deprivation (OGD)-induced myocardial cell injury model were constructed to explore the underlying role of AMPK/SIRT1 pathway in Arctigenin-mediated effects. The experimental data in our study demonstrated that Arctigenin ameliorated OGD-mediated cardiomyocytes apoptosis, inflammation and oxidative stress in a dose-dependent manner. Besides, Arctigenin activated AMPK/SIRT1 pathway and downregulated NF-κB phosphorylation in OGD-treated cardiomyocytes, while inhibiting AMPK or SIRT1 by the Compound C (an AMPK inhibitor) or SIRT1-IN-1 (a SIRT1 inhibitor) significantly attenuated Arctigenin-exerted protective effects on cardiomyocytes. In the animal experiments, Arctigenin improved the heart functions and decreased infarct size of the AMI/R-rats, accompanied with downregulated oxidative stress, inflammation and apoptotic levels in the heart tissues. What’s more, Arctigenin enhanced the AMPK/SIRT1 pathway and repressed NF-κB pathway activation. Taken together, our data indicated that Arctigenin reduced cardiomyocytes apoptosis against AMI/R-induced oxidative stress and inflammation at least via AMPK/SIRT1 pathway.